ダイ5ジ ナンキョク チイキ カンソクタイ キショウ ブモン センジョウ カンソク ガイホウ - 田島, 成昌; タジマ, ナリマサ; 守田, 康太郎; モリタ, ヤスタロウ; TAJIMA, Narimasa; MORITA, Yasutaro (国立極地研究所, 1962)
P(論文) This paper briefly reports the result of the weather analysis carried out on m/s SOYA during the relief operation of J.A.R.E. V in the Antarctic in the summer of 1960-1961. The synoptic data were collected through the interception of the wireless weather transmission listed in Table 1 and Fig. 1. The meteorological condition in the vicinity of Lutzow-Holm Bay in this season was quite favourable and was the best of the five summers from 1957 to 1961. The maximum wind velocity did not exceed 15 m/s and the amount of lower cloud was extremely small. The weather recorded on m/s SOYA is summarized in Tables 2 and 3. The frequencies of wind velocity and of the amount of lower cloud for this summer are compared with those for the previous summers, as shown in Figs. 2 and 3. The data in these figures are based on the observations at Syowa Base with respect to the common period for the five summers. The synoptic meteorological pattern, relating to the extraordinary good weather of this summer, was analysed through the weather maps prepared on m/s SOYA; and it was concluded as follows: a) In middle summer, from early January to middle February, the polar cap anticyclone was not powerful enough to control over the Antarctic coastal waters. The anticyclonic ridge, however, was apt to stagnate over the area of Queen Maudland with the meridional axis connecting the polar cap anticyclone with the meridional one. This ridge prevented developement of cyclones which ordinarily tend to appear over the waters around Bouvet Island and move southeastward to attack Lutzow-Holm Bay. Trajectories of the major cyclones in this summer are plotted in Fig. 4. It is noticed that the characteristic features of the trajectories resemble those in the summer of 1957 (Fig. 5a), when we experienced another favourable weather in the area concerned. On the contrary, the trajectories in the summer of 1958, when the worst weather was experienced, revel a different character as the well-developed cyclones frequently crossed the line of latitude ...